2013
DOI: 10.1152/ajpendo.00032.2013
|View full text |Cite
|
Sign up to set email alerts
|

High glucose levels reduce fatty acid oxidation and increase triglyceride accumulation in human placenta

Abstract: 25Aim/hypothesis: Placenta of women with gestational diabetes mellitus (GDM) exhibits an 26 altered lipid metabolism. The mechanism by which GDM is linked to alterations in placental lipid 27 metabolism remains obscure. We hypothesized that high-glucose levels reduce mitochondrial fatty 28 acid oxidation (FAO) and increase triglyceride accumulation in human placenta. 29 Methods:To test this hypothesis, we measured FAO, fatty acid esterification, de novo fatty 30 acid synthesis, triglyceride levels and carnitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 48 publications
10
77
0
Order By: Relevance
“…In particular, this should be informed by more detailed experimental analysis of metabolic subcompartments in placental tissue. altered in diabetic pregnancy (40,41). Although the perfused placenta is a highly useful model, it must be remembered that there will be many differences in vivo, including the concentrations of maternal and fetal substrates and hormones, which may both influence placental metabolism and transport.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, this should be informed by more detailed experimental analysis of metabolic subcompartments in placental tissue. altered in diabetic pregnancy (40,41). Although the perfused placenta is a highly useful model, it must be remembered that there will be many differences in vivo, including the concentrations of maternal and fetal substrates and hormones, which may both influence placental metabolism and transport.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, obese mice had decreased blastocyst expression of Slc2a1 compared with non-obese mice, suggesting a downregulation of glucose uptake when fatty acid levels are elevated (Bermejo-Alvarez et al 2012). Elevated serum glucose levels in pregnant women correspond to reduced levels of CPT1 activity in placental extracts, thereby decreasing FAO (Visiedo et al 2013). Furthermore, overexpression of glucose transporter Slc2a1 in mouse cardiac tissue increases glucose uptake and oxidation while decreasing FAO, despite a high supply of fatty acids (Yan et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…154 A recent study reported that placental explants from GDM pregnancies had a two-to 155 three-fold higher glucose uptake and a 50% reduction in fatty acid oxidation [47]. Placentae 156 from normoglycemic pregnancies cultured in high glucose had reduced fatty acid oxidation, 157 along with increased esterification and accumulation of triglycerides [37]. The mechanism 158 proposed was inhibition of carnitine palmitoyltransferase (CPT1) activity by a glucose-159 derived by-product, malonyl-CoA.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Placental NEFA esterification into triglycerides is thought to be increased in 277 pregnancies complicated by hyperglycemia and/or obesity as a regulatory step to limit fatty 278 acid transfer to the fetus [37]. However, there is no direct evidence to support this notion 279 and earlier studies indicate that de novo fatty acid synthesis is not a significant contributor 280 to triglyceride accumulation in diabetic placentae [84].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%